Efficacy and safety of prophylactic superselective embolization for angiomyolipoma at the renal hilum. Issue 5 (May 2021) - Inoue, Tatsuro; Zhang, Xixi; Kuwatsuru, Ryohei; Okada, Shingo; Kato, Hitomi; Ozu, Hiromi; Yanagida, Masataka; Yamashiro, Yuki
Objective: This study investigated the efficacy and safety of superselective transcatheter arterial embolization for angiomyolipoma at the renal hilum. Methods: Between August 2012 and January 2015, 13 patients with 16 angiomyolipomas at the renal hilum underwent initial, prophylactic, superselective transcatheter arterial embolization. The patients were followed by computed tomography or magnetic resonance imaging, and volume-reduction ratios after embolization were measured. Results: The mean or median post-embolization volume reduction ratios were 23% (follow-up duration, 1–2 months), 55% (3–6 months), 55% (7–12 months), 66% (1–2 years), 67% (2–3 years), and 54% (>3 years). After initial embolization, none of the 16 tumors bled or required surgery; two (13%) tumors recurred; and three (19%) tumors received repeat embolization. Estimated glomerular filtration rates were not decreased at medians of 7 days (near the time of discharge) and 39 days (first clinical follow-up) post-procedure, compared with baseline. Except for post-embolization syndrome, no procedure-related complications occurred. Conclusions: Superselective embolization for renal hilar angiomyolipoma is safe and kidney-preserving, with good tumor volume reduction and bleeding prevention.